IN VITRO ANTIBACTERIAL EFFECT OF BREADFRUIT LEAF EXTRACT AGAINST STREPTOCOCCUS SANGUINIS ATCC 10556 BIOFILM - NADIA, VAZA; UTAMI, SRI; FARIDA, RATNA (International Journal of Applied Pharmaceutics, 2019)
Objective: Evidence indicates that breadfruit leaf extract may have antibacterial properties. In terms of bacterial plaque, Streptococcus sanguinis is known as an early agent of its formation. The purpose of this study was to analyze the antibacterial effects of breadfruit leaf extract on the growth of S. sanguinis. Methods: S. sanguinis ATCC 10556 was cultured in 96-well plates and was incubated at 37°C for 20 h (the accumulation phase) or 24 h (the maturation phase). Then, breadfruit leaf extract was added at concentrations of 5, 10, 20, 40, 80, and 100%. The viability of S. sanguinis was evaluated using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay at a wavelength of 490 nm. Results: Our results demonstrated that the viability of S. sanguinis, after exposure to the breadfruit leaf extract at all concentrations, during the accumulation and maturation phases was lower than the control group (p<0.05). In addition, the viability of S. sanguinis after exposure to the breadfruit leaf extract at concentrations of 20, 80, and 100% during the accumulation phase was lower than that observed during the maturation phase. Conclusion: Collectively, our novel findings should provide insight into the potential of breadfruit leaf extract to positively affect oral and dental health.